Aprioristic versus empirical linguistics: the case of Balto-Slavic accentuation - Kortlandt, Frederik (Baltistica, 2019)
The reconstruction of Balto-Slavic accentuation requires a careful examination of the data rather than the postulation of wild ideas in need of countless additional hypotheses in order to eliminate the counter-evidence.
Keywords: Balto-Slavic; historical accentology